2018
DOI: 10.1016/j.rvsc.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic mesenchymal stem cell transplantation in healthy equine superficial digital flexor tendon: A study of the local inflammatory response

Abstract: The superficial digital flexor tendon (SDFT) is a structure frequently affected by injuries in high-performance athletic horses, and there are limited therapeutic options. Regenerative medicine has evolved significantly in treating different illnesses. However, understanding the cellular behaviour during mesenchymal stem cell (MSC) transplantation in healthy tissues is not fully known yet. To address the inflammatory response induced by allogeneic MSC transplantation, this study evaluated the local inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…However, MSCs including ASCs reportedly have an immunomodulatory property, which allows allogenic MSC implantation. [37][38][39][40] The total number of the ASCs that implanted in this study was 0.4 M/shoulder, which is relatively small compared to numbers reported in previous studies. This may be the reason we failed to detect positive impact of ASCs on the biomechanical healing of RTC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, MSCs including ASCs reportedly have an immunomodulatory property, which allows allogenic MSC implantation. [37][38][39][40] The total number of the ASCs that implanted in this study was 0.4 M/shoulder, which is relatively small compared to numbers reported in previous studies. This may be the reason we failed to detect positive impact of ASCs on the biomechanical healing of RTC.…”
Section: Discussionmentioning
confidence: 64%
“…While allogenic implantation allows “off‐the‐shelf” therapeutic strategy without any donor site morbidity, a harmful allogeneic immune reaction may reduce the therapeutic beneficial effect of ASC implantation. However, MSCs including ASCs reportedly have an immunomodulatory property, which allows allogenic MSC implantation …”
Section: Discussionmentioning
confidence: 99%
“…Altogether, this information provides a promising preliminary data. In this sense, there are many reports regarding the protective effect of MSCs through their anti‐inflammatory, anti‐reactive oxygen species and anti‐apoptotic effect in different tissues (Brandão et al, ; Da Silva Meirelles, Fontes, Tovas, & Caplan, ; Madrigal, Rao, & Riordan, ; Salgado, Reis, Sousa, & Gimble, ). Additionally, Hsiao et al () reported therapeutic benefits on rat with induced testicular torsion after stem cells therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The tendons are among the tissues most affected by pathologies associated with overloading (Tyrnenopoulou et al, 2016). The damaged tendon recovers, however its function remains altered, implying a substantial risk of a new injury (Violini et al, 2009;Brandão et al, 2018). The probability of recurrence of tendonitis may be as high as 43 % if the horse returns to racing (Roth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Autologous forms of MSC present an additional advantage, in that they do not induce an auto-immune response in the host (Bianchi de Di Risio et al, 2004;Brandão et al). Adipose tissue is derived from embryonic mesenchyme, and in the adult, contains a stroma which can easily be isolated, with little stress for the animal and rapid recovery (Zuk et al, 2001(Zuk et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%